Motor intervention program for school children with signs of developmental coordination disorder - DCD Programa de intervenção motora para escolares com indicativo de transtorno do desenvolvimento da coordenação - TDC - da Silva E.V.A.* (2011)
This study aimed to verify the effects of a motor intervention program for students with signs of DCD. Six 10 year-old students, both male and female, who were registered at a municipal school in the interior of the state of Santa Catarina participated in the study. Motor capacity was measured using the Movement Assessment Battery for Children (MABC-2), one of the most commonly used instruments for assessing children's movement difficulties. The test encompasses the age groups of 3 to 16 years; for each age group, eight tasks are grouped into three skill categories: manual skill, throw and catch, balance. The interventions were based on the Developmental Physical Education approach in school environments. The sessions were done individually with 20 motor intervention sessions for each student, in a total of 120 sessions, frequency of two weekly classes with 45 minutes duration. The Wilcoxon test with the statistical package SPSS 13.0 for Windows was used for data interpretation. The results showed statistically significant differences after motor intervention (p <0,05). Regarding the results of motor skill performance, it was found that balance skills presented better improvement results after intervention, revealing that a motor intervention proposal was effective with children with signs of DCD. This study revealed the importance of promoting students with motor disabilities participation in intervention programs in order to monitor their motor development progress, so as to improve movement difficulties both in sports and in daily activities.